Língua(s) de fronteira: o ensino da Língua Espanhola em Guaíra, Paraná - Ribeiro, Simone Beatriz Cordeiro (2015)
Reflecting on language policies and language planning in development and in practice it is an attempt to understand how they are being thought and executed. As Language Policy is a field of study that, when as the conductor of the public concern and of the emerging need of a nation, it manages the actions and reflections regarding the field of languages. The drawing up of a language planning that meets community interests is a necessity, along with the fact of being a responsibility of public authorities, since it is indispensable to correlate these fields with approaches related to linguistic rights, due to the contemporary scenario in which Language teaching and learning, most of the time, is a place where local or regional reality are being ignored. Therefore, considering this regard, this Thesis proposes to study the Spanish Language in the municipality of Guaíra - Paraná as a Border Language in order to identify, to discuss and to argue in favor of a language planning and policy compatible with the linguistic context of this municipal district. Hence, this research process indexed by Applied Linguistic, under the critical bias, supported by Pennycook (1998, 2006), Rajagopalan (2003), Signorini and Cavalcanti (1998), and Moita Lopes (2006), plus Sociolinguistic studies, Labov (1983, 1986, 2008), Tarallo (2007), and others, under Language Policies, through studies of Calvet (2007 [1987]), Oliveira (2010), Pereira and Costa (2011), Savedra and Lagares (2012), Rajagopalan (2013), Nicolaides et al. (2013) and von Borstel (2013), aiming a linguistic and political approach of local and regional nature which considers that teaching the said Modern Foreign Language, in this region of geographic border discourse of Paraguay, and, also, under the factor of historical region, as either in matters of Spanish settlement and colonization after the discovery of America, with focus on the municipal district of Guaíra, Paraná, or the strong presence of Spanish, Argentinians and, mostly, Paraguaians during the Matte Larangeira Company's export of maté. Thus, for the purpose of analysis, the applied method was in situ research using 33 semi-structured interviews, applying an script based on reflections and readings of qualitative approach, from theories by Flick (2004), Lüdke and André (1986), and others. According to the language policy applied in the above said municipal district where teaching of the English Language is a priority, this work justifies and argues, based on the context experienced by its citizens, the importance and common sense of introducing the Spanish Language in the educational curriculum of primary schools, beginning years, of the Brazilian educational system, enhancing the relevance of having an applied approach that involves the whole resulting contemporary problem, coached not only by theories but also by problems in order to understand language and sociocultural borders